The development and reproduction of grape phylloxera (Daktulosphaira vitifoliae Fitch) strains of Hungarian vine-districts in root-bioassays - L. Tóth, H.; Horváthné Baracsi, L.; Kocsis, L. (International Journal of Horticultural Science, 2004)
The root bioassay method allows for 4-6 week continuous observation of grape phylloxera feeding on the grape root. 10 Hungarian phylloxera strains were compared on susceptible Vitis vinifera cv. Chardonnay and the resistant rootstocks of V. berlandieri x V. riparia Teleki 5C and V. berlandieri x V. rupestris Georgikon 121 in in vitro observations. The strains originated from Villany and Eger (Figure 3) had higher reproduction on the root of V. berlandieri x V. riparia Teleki 5C (201 and 119 eggs) and were more aggressive than the others (average production 10 eggs). The continuous high level of survival, development and reproduction of the Eger strain on Teleki 5C (V. berlandieri x V. ripuria) until day 46 may be due to adaptation.